Social Responsibility, Sustainability and the Role of Entrepreneurship - Kumar Gupta, Jitendra (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Good ethics are aware that you have a positive economic impact on business performance. Statistics support the assumption that ethics, value, integrity and responsibility require in the modern workplace. Consumer organizations in society, good ethics, are the result of good business management. Ethics are important because they prove the good business sense. Keywords: Ethics, Ethical Discipline Professional Ethics, Ethical Behavior.